Antioxidant effects of resveratrol in the cardiovascular system. (6th May 2016) - Xia, Ning; Daiber, Andreas; Förstermann, Ulrich; Li, Huige
Abstract : The antioxidant effects of resveratrol (3, 5, 4 ' ‐trihydroxy‐ trans ‐stilbene) contribute substantially to the health benefits of this compound. Resveratrol has been shown to be a scavenger of a number of free radicals. However, the direct scavenging activities of resveratrol are relatively poor. The antioxidant properties of resveratrol in vivo are more likely to be attributable to its effect as a gene regulator. Resveratrol inhibits NADPH oxidase‐mediated production of ROS by down‐regulating the expression and activity of the oxidase. This polyphenolic compound reduces mitochondrial superoxide generation by stimulating mitochondria biogenesis. Resveratrol prevents superoxide production from uncoupled endothelial nitric oxide synthase by up‐regulating the tetrahydrobiopterin‐synthesizing enzyme GTP cyclohydrolase I. In addition, resveratrol increases the expression of various antioxidant enzymes. Some of the gene‐regulating effects of resveratrol are mediated by the histone/protein deacetylase sirtuin 1 or by the nuclear factor‐E2‐related factor‐2. In this review article, we have also summarized the cardiovascular effects of resveratrol observed in clinical trials. Linked Articles: This article is part of a themed section on Redox Biology and Oxidative Stress in Health and Disease. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.12/issuetoc